2019
DOI: 10.1002/humu.23863
|View full text |Cite
|
Sign up to set email alerts
|

LOVD–DASH: A comprehensive LOVD database coupled with diagnosis and an at‐risk assessment system for hemoglobinopathies

Abstract: Hemoglobinopathies are the most common monogenic disorders worldwide. Substantial effort has been made to establish databases to record complete mutation spectra causing or modifying this group of diseases. We present a variant database which couples an online auxiliary diagnosis and at‐risk assessment system for hemoglobinopathies (DASH). The database was integrated into the Leiden Open Variation Database (LOVD), in which we included all reported variants focusing on a Chinese population by literature peer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…For example, rs67385638, rs11036474 and rs10128556 were more strongly associated with HbF levels than rs7482144. Conditional analysis showed that rs11036474 and rs10128556 were the most independently-associated variants found in the HbF-1 and HbF-2 subgroups while rs11036474 has not been reported in other populations except in China [ 28 ]; our findings on rs10128556 corroborate those of Galarneu et al [ 6 ].…”
Section: Discussionsupporting
confidence: 88%
“…For example, rs67385638, rs11036474 and rs10128556 were more strongly associated with HbF levels than rs7482144. Conditional analysis showed that rs11036474 and rs10128556 were the most independently-associated variants found in the HbF-1 and HbF-2 subgroups while rs11036474 has not been reported in other populations except in China [ 28 ]; our findings on rs10128556 corroborate those of Galarneu et al [ 6 ].…”
Section: Discussionsupporting
confidence: 88%
“…The test we developed is focused on the Southern Chinese population where there are 46 common variants. Based on the positioning of the targeting primers, we suggest that the current test should be able to detect any of the known 290 pathogenic variants 16 . However, to improve the accuracy for the detection of rarer HBB variants located in the 5′ proximal and 3′ distal regions as well those deep within intron 2, it will be necessary to use additional targeting primers, positioned to avoid common SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the positioning of the targeting primers, we suggest that the current test should be able to detect any of the known 290 pathogenic variants. 16 However, to improve the accuracy for the detection of rarer HBB variants located in the 5 0 proximal and 3 0 distal regions as well those deep within intron 2, it will be necessary to use additional targeting primers, positioned to avoid common SNPs. We estimate that in addition to the nine targeted primers used in this version of the assay, a minimum of a further three inverse primer pairs would be needed to guarantee full mutation coverage of the entire HBB gene.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven types of β-globin gene cluster deletions have been reported in the Chinese (Fig. 1 .1-A, Table 1 ) 5 10 . Coinheritance of these deletions with other β-thalassemias or Hb variants results in phenotypes ranging from asymptomatic to β-thalassemias major 11 .…”
Section: Introductionmentioning
confidence: 99%